IMPACT OF URBAN EXPANSION ON SURFACE TEMPERATURE INBAGHDAD, IRAQ USING REMOTE SENSING AND GIS TECHNIQUES - Saleh, Salah A H; Saleh, Salah A H (Al-Nahrain Journal of Science, 2010)
Baghdad city has experienced a rapid urban expansion over the last decades due to accelerated economic growth. This paper reports an investigation into the application of the integration of remote sensing and geographic information systems (GIS) for detecting urban built up growth for the period 1961-2002, and evaluate its impact on surface temperature in Baghdad city. The purpose of this study is to analysis and verifies the spatial distribution property of the surface temperature with urban spatial information, related with land cover / land use and NDVI using remotely sensed data and GIS. Surface temperature, land cover pattern and NDVI wereextracted from Landsat7 ETM + data. Then surface temperatures, was linked to land use data of Baghdad region for further investigations of the relationship between temperature behavior and urban structures. The Normalized Difference Vegetation Index (NDVI) was used to examine the relation between thermal behavior and vegetation cover amount. The results showed that the negative average correlation more than 85 % was identified by the results from the correlation and regression analysis of the extracted surface temperature from Landsat data image with NDVI. Also this research verified the distribution of urban surface temperature was very different depends on various land cover type of surrounding areas. Water and forest cover types show low day temperature differences compared to residential, commercial cover types.The integration of remote sensing and GIS was found to be effective in monitoring and analyzing urban growth patterns and in evaluating urbanization impact on surface temperature.